Case report: Identification of acute promyelocytic leukemia during osimertinib resistance followed by granulocyte colony-stimulating factor and pembrolizumab - Tian, Huohuan; Yang, Linhui; Hou, Wang; Wu, Yu; Dai, Yang; Yu, Jiang; Liu, Dan (Frontiers in Oncology, 2023)
Background The occurrence of acute promyelocytic leukemia (APL) during the management of lung cancer is rare and life-threatening. It was mainly reported to be secondary to chemoradiotherapy. A few studies reported an increased incidence of therapy-related acute promyelocytic leukemia (t-APL) after gefitinib became available. Case presentation We reported a patient who developed thrombocytopenia after receiving oral osimertinib in combination with intensity-modulated radiotherapy (IMRT). For half a year, she had an unrecoverable low platelet count, which progressed to concomitant leukopenia and the transient appearance of orthochromatic normoblasts in the peripheral blood test, indicating a dormant myeloid disorder. Due to simultaneous resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKI), pembrolizumab and granulocyte colony-stimulating factor (G-CSF) were administered, revealing prominent signs of hematological malignancy in a peripheral blood test that was later identified as t-APL. Conclusion In general, patients undergoing EGFR-TKI combined with local radiotherapy should be concerned about their hematological assessment. If patients exhibit unrecoverable abnormalities in routine blood tests, a secondary nonsolid malignancy other than myelosuppression should be considered, and further lung cancer treatment should be discontinued.